2015
DOI: 10.2174/1568026615666150610142234
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nicotinamide Phosphoribosyltransferase in Cerebral Ischemia

Abstract: Recombinant tissue plasminogen activator is the only drug approved for the clinical treatment of acute ischemic stroke. Thus, there is an urgent unmet need for novel stroke treatments. Endogenous defense mechanisms against stroke may hold the key to new therapies for stroke. A large number of studies suggest that nicotinamidephosphoribosyl-transferase (NAMPT) is an attractive candidate to improve post-stroke recovery. As a multifunctional protein, NAMPT plays important roles in immunity, metabolism, aging, inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…iNAMPT over-expression as well as increased circulating levels of eNAMPT were documented in metabolic/inflammatory conditions including obesity, type 2 diabetes, metabolic syndromes, atherogenic inflammatory diseases, therefore supporting a role for eNAMPT as a potential biomarker of cardio-cerebro-vascular disorders (157)(158)(159)(160). Enhanced eNAMPT levels are also described in kidney transplantation recipients (161), polycystic ovary syndrome (162), preeclampsia (163), and acute coronary syndrome (158,164).…”
Section: Nampt and Naprt As Biomarkers Of Chronic And Acute Inflammatmentioning
confidence: 90%
“…iNAMPT over-expression as well as increased circulating levels of eNAMPT were documented in metabolic/inflammatory conditions including obesity, type 2 diabetes, metabolic syndromes, atherogenic inflammatory diseases, therefore supporting a role for eNAMPT as a potential biomarker of cardio-cerebro-vascular disorders (157)(158)(159)(160). Enhanced eNAMPT levels are also described in kidney transplantation recipients (161), polycystic ovary syndrome (162), preeclampsia (163), and acute coronary syndrome (158,164).…”
Section: Nampt and Naprt As Biomarkers Of Chronic And Acute Inflammatmentioning
confidence: 90%
“…Nicotinamide adenine dinucleotide (NAD + ) is a classic energy metabolite that synthesized from its precursors (nicotinic acid and nicotinamide) by the rate-limiting enzyme nicotinamide phosphoribosyl transferase (NAMPT) 11, 12 . NAD + positively regulates the activity of silent mating type information regulation 2 homolog 1 (Sirt1), and plays critical roles in neuroprotection after ischemic stroke 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also suggested that Nampt can influence autophagy [ 13 , 14 ], while changes in autophagy levels are known to affect ECM metabolism [ 16 , 35 ]. Therefore, we speculated that Nampt affected ECM metabolism by modulating autophagy, and subsequently examined the effects of Nampt on autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, we hypothesized that Nampt might affect ECM degradation of SUI fibroblasts. It is also noteworthy that Nampt is implicated in various immune conditions and nerve injuries due to its ability to manipulate apoptosis, metabolic activities, and autophagy [ 13 ]. Similarly, another study documented that inhibition of Nampt led to attenuation of inflammatory symptoms in sepsis by virtue of enhancing autophagy [ 14 ].…”
Section: Introductionmentioning
confidence: 99%